Surface entrapment of chitosan on 3d printed polylactic acid scaffold - Zakaria, Nor Hidayah (2018)
This thesis reports a surface entrapment of chitosan on 3D printed PLA scaffold which has the potential use in promoting bone regeneration. The 3D scaffold was designed using SolidWorks and printed by Up Plus 3D printer and then incorporated with chitosan. The entrapped scaffold time was varied from 5 to 90 s. The scaffold was characterized in respect of its mechanical and surface properties. Compressive test showed a higher compressive modulus properties in neat 3D printed PLA scaffolds and an optimum value of 22248 MPa at 15 s of chitosan immersion. The Fourier-transform infrared spectroscopy peak revealed an existence of biomacromolecule and new absorption peaks at 3357 and 1618 cm-1 compared to neat PLA on the scaffold while water contact angle showed an increase in hydrophilicity as entrapment time increased. The confocal laser scanning microscopy revealed the existence of entrapment areas approximately 8??m in depth. The scanning electron microscopy showed clearly 3D scaffold with high porosity, uniform distribution chitosan and a controlled and repetitive architecture on entrapped 3D printed scaffold. Immersion of neat and entrapped 3D printed PLA scaffold in simulated body fluid for 14 days resulted the formation of fully covered apatite layers on the surface of entrapped PLA scaffold whereas no change was observed in neat PLA scaffold. Overall, the mechanical and surface properties results showed the suitability of the combination of method and materials to develop 3D porous scaffold and their initial biocompatibility, both being valuable characteristic for tissue engineering applications.